Interactions of the L, P and Np Proteins of the Newcastle Disease Virus - Adzahar, Noor Suhana (2006)
The large (L) and phospho- (P) proteins together with the nucleocapsid (NP) protein of Newcastle disease virus (NDV) are involved in the transcription and replication of the viral genome. The L protein interacts with the P protein to form the active RNA dependent RNA polymerase complex which then acts on the ribonucleoprotein (NP:RNA) comprising the single stranded negative RNA genome which is tightly bound to the NP protein. Amino acid sequence alignment of the L proteins of several nonsegmented negative stranded RNA viruses revealed six highly conserved domains described as Domains I to VI which were proposed to specify the essential activities common to the polymerases of these virus. In this study, the individual domains of the L gene of NDV strain AF2240 were cloned separately into pCITE2b plasmid expression vector. An in vitro protein binding assay was used to determine the conserved domains on L protein that interact with the purified NP protein. The full length purified NP protein was immobilized on a solid phase and then interacted with radiolabelled [35S]-L domains synthesized in rabbit reticulocyte lysates. The interaction affinity was quantitated by measuring the radioactivity that was retained on the solid phase. Domain III, which is located between amino acids 631-861, was shown to be highly interactive with the NP protein. In addition, Domains II (amino acid 502 to 607), IV (amino acid 904 to 1071) and V (amino acid 1488 to 1597) showed weak interaction with the NP protein. On the other hand, the interactions between in vitro translated L protein domains with the P protein were determined by the immunoprecipitation method. In this approach, the L-P complexes which formed in the mixture were captured with anti-myc monoclonal antibody conjugated to protein G agarose. These complexes were precipitated and analysed by autoradiography. Domain V was observed to exhibit the strongest binding with P whereas Domains III and IV showed weaker binding capacities. In conclusion, the core domains of L comprising Domains III, IV and V were interacted with both P and NP proteins which are involved in transcription and replication, but their levels of interactions differed.